Thymol and eugenol against Rhipicephalus sanguineus sensu lato engorged females: Biological, histopathological and bioinformatic analysis - Silva, Isabela Santos; Vale, Letícia; Coutinho, Ana Lúcia; Sousa, Lainny Jordana Martins Pereira e; Marchesini, Paula; da Silva Matos, Renata; Anholeto, Luís Adriano; Mathias, Maria Izabel Camargo [UNESP]; Ferreira, Lorena Lopes; Arruda, Walquiria; Monteiro, Caio (Elsevier, 2023)
The aim of this study was to evaluate the reproductive biology and histopathology of the ovaries of engorged females of Rhipicephalus sanguineus sensu lato exposed to combinations of thymol and eugenol, as well as to evaluate in silico the possible interactions of thymol and eugenol in tick cell membranes. To evaluate the tick reproductive biology, the adult immersion test (AIT) was performed, in which the engorged females were immersed in solutions of thymol and eugenol, combined or alone, at concentrations of 2.5 and 5.0 mg/mL. Two control groups (water and 3% DMSO) were also performed. The ticks were kept in a controlled chamber (B.O.D - 27 ± 1 °C and 80% ± 5% RH) to evaluate egg production and viability. To perform the ovaries histopathological evaluation, females were immersed in combination of thymol and eugenol (each at 2.5 and 5.0 mg/mL) and control (water and 3% DMSO) solutions. After immersion, the females were kept in B.O.D (27 ± 1 °C and RH of 80% ± 5%) for four days, they were dissected and the ovaries processed for histological analysis. In addition, an in silico analysis was performed using PASS online® software to predict probability activity (PA) of thymol and eugenol in cell membranes. The treatment with the combination of thymol and eugenol (each at 5.0 mg/mL) caused a reduction (p < 0.01) in oviposition, while the treatments with thymol (5.0 mg/mL) and combination of thymol and eugenol (5.0 mg/mL) reduced (p < 0.05) the egg viability. The treatment with combination of thymol and eugenol (5.0 mg/mL) resulted in a control percentage of 99.9%, while in the other treatments, control percentages below 56% were observed. Oocytes from the females exposed to the combinations of thymol and eugenol (each compound at 2.5 mg/mL) showed histopathological changes, except on oocyte V, while those treated with these compounds alone at 2.5 mg/mL, did not reveal any change. Changes in the shape of the oocyte, presence of vacuoles in the cytoplasm and germinal vesicle, reduction and fusion of yolk granules and rupture of some oocytes were observed. In silico analysis, showed that these compounds can act as membrane permeability inhibitors, membrane permeability agonists, membrane integrity antagonists and apoptosis agonists. We conclude that the combination of thymol and eugenol causes changes in the reproductive biology and morphophysiology of engorged females oocytes. The in silico analysis using thymol and eugenol revealed the possibility of disorganization in the cell membranes, a fact that may explain the histopathological alterations observed.
Keywords: Brown dog tick; Essential oil; Histology; in silico analysis; Monoterpene; Phenylpropanoid